SELF MANAGEMENT OF STUDENT (Marriage during the Lecture) - Darmawan, Oki (Pascasarjana IAIN Kudus, 2013)
Based on this research the factors driving perform marriage during the lecture are:1) In order to avoid promiscuity, 2) More motivatedto learn,3) avoid slander in society, 4) ease the burden of parents, 5)want to be independent 6) have found the perfect match,7) parentsstill help while study, 8) Draw closer to Allah SWT to run the Sunnahof the Prophet. Marriage during the lecture did not inhibit study,learning, academic achievement (IP value), but the activity in the organization on campus have started to be reduced. The married student more in order to continue to maintain the health to face campus activities and can organize and devote time to family andstudies, for the students who have not yet married:it is advisablefor those who are ready to get married, do not procrastinate tomarried, but must have the material and spiritual preparation thatmature. For parents: authors are looking forward to the parentswho have children who are interested in getting married shouldprovide support both materially and spiritually as well as guidanceto their sons and daughters who will enter the marriage becausemarriage proven through this research does not inhibit the studyKeywords: Student, Marriage, Lecture